Antimicrobial and anti-adhesive potential of a biosurfactant Rufisan produced by Candida lipolytica UCP 0988 - Rufino, R. D. (2011)
In the last years, researches developed with biosurfactants for application in the medical area have been revealing the promising biological activities of these biomolecules. In this work the antimicrobial and anti-adhesive properties of a biosurfactant Rufisan isolated from the yeast Candida lipolytica UCP 0988, growth in a medium supplemented with ground nut refinery residue was determined against several microorganisms. The biosurfactant was able to reduce the water surface tension from 70 to 25.3mN/m and showed a critical micelle concentration (CMC) of 0.03%. The biosurfactant was isolated after 72 h of fermentation and was tested in concentrations varying from 0.75 to 12 mg/l. The highest antimicrobial activities were observed against Streptococcus agalactiae, Streptococcus mutans, Streptococcus mutans NS, Streptococcus mutans HG, Streptococcus sanguis 12, Streptococcus oralis J22 at a concentration superior to the biosurfactant critical micelle concentration. Moreover, the biosurfactant showed anti-adhesive activity against most of the microorganisms tested. As far as we know, this is the first compilation of data on antimicrobial and anti-adhesive activities of a biosurfactant obtained from a Candida strain against such a broad group of microorganisms. The results obtained in this work showed that the biosurfactant from C. lipolytica is a potential antimicrobial and/or anti-adhesive agent for several biomedical applications